THE EFFECT OF PICTURE AND PICTURE ON STUDENTS' ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Joshua Marthin Simbolon (Universitas Suryakancana, 2021)
This study aims to determine whether the picture and picture method has a significant effect on the text description writing skills of students at SMP Al-Hidayah Medan or not. This study used quantitative method. The results of this study were obtained from the t test with a significance level of α = 0.05 and the accumulated results of two different groups, namely the experimental group (which applied picture and picture) and the control group (which did not use picture and picture). In the pre-test experimental group the average result obtained was 51.15 while the average post-test result was 83.75. In the pre-test control group the average result obtained was 53.45, while the average post-test result was 79.65. The results of the hypothesis obtained are ttest = 2.831 ≥ ttable = 1.685. This proves that the value of the experimental group is better than the control group, so it can be concluded that the use of pictures and picture methods can have a significant impact on students' descriptive writing skills.